2017
DOI: 10.1111/gbb.12391
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase‐1b deletion confers depression‐like behavioral resistance separate from stress‐related effects in mice

Abstract: Phosphodiesterase-1b (Pde1b) is highly expressed in striatum, dentate gyrus, CA3, and substantia nigra. In a new Floxed Pde1b × CreCMV global knock-out (KO) mouse model we show an immobility resistance phenotype that recapitulates that found in constitutive Pde1b KO mice. We use this new mouse model to show that the resistance to acute stress-induced depression-like phenotype is not the product of changes in locomotor activity or reactivity to other stressors (learned helplessness, novelty suppressed feeding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Constitutive (Reed et al, 2002; Siuciak et al, 2007) as well as conditional (Hufgard et al, 2017) PDE1B knockout mice exhibit altered exploratory activity in the open field. We therefore asked if selectively targeting PDE1B in hippocampus of adult mice causes locomotor effects that may confound analysis of a role in memory using the current approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutive (Reed et al, 2002; Siuciak et al, 2007) as well as conditional (Hufgard et al, 2017) PDE1B knockout mice exhibit altered exploratory activity in the open field. We therefore asked if selectively targeting PDE1B in hippocampus of adult mice causes locomotor effects that may confound analysis of a role in memory using the current approach.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Schizophrenia, PDE1 inhibitors may have therapeutic benefits in mild-cognitive impairment associated with Parkinson’s disease (Parkinson’s MCI), Alzheimer’s disease, and cognitive deficits in major depressive disorder (MDD; Hufgard et al, 2017). However, additional work will be required to determine the mechanistic and behavioral impact of PDE1 inhibition in the context of disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PDE1B-deletion mice manifest a compensatory increase in PDE10A in the striatum (Hufgard et al, 2017a). In addition, the immobility-resistant phenotype of PDE1B-deficient mice is detected when the PDE1B gene deletion occurs during postnatal days 0 or 32 but not during adulthood (Hufgard et al, 2017b). Furthermore, PDE1B-deficient mice display spatial learning and memory impairments in the Morris water maze task (Reed et al, 2002), while PDE1 inhibitors improve learning and memory function in several behavioral tasks in mice and rats (Li et al, 2016a;Snyder et al, 2016;Pekcec et al, 2018;McQuown et al, 2019).…”
Section: Pde1 Inhibitor Is Effective In Schizophrenia Modelsmentioning
confidence: 99%
“…Syndig1l harbors epigenetic CpG-related single nucleotide polymorphisms associated with AD in Hispanic populations (Ma et al, 2024). Pde1b , encoding a phosphodiesterase 1, has been linked to motor activity and spatial learning (Reed et al, 2002), identified in motor control in striatum of transgenic mice of Huntington’s (Hebb et al, 2004) and involved in depression-like behaviors in response to stress in mice (Hufgard et al, 2017). Overexpression of Pde1b in dopamine D1 receptor-containing striatal MSNs attenuated the locomotor response to cocaine in female mice but not males (Teague et al, 2024).…”
Section: Discussionmentioning
confidence: 99%